2014
DOI: 10.1111/jsr.12220
|View full text |Cite
|
Sign up to set email alerts
|

Subjective–objective sleep discrepancy among older adults: associations with insomnia diagnosis and insomnia treatment

Abstract: SUMMARY Discrepancy between subjective and objective measures of sleep is associated with insomnia and increasing age. Cognitive behavioral therapy for insomnia improves sleep quality and decreases subjective-objective sleep discrepancy. This study describes differences between older adults with insomnia and controls in sleep discrepancy, and tests the hypothesis that reduced sleep discrepancy following cognitive behavioral therapy for insomnia correlates with the magnitude of symptom improvement reported by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
97
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 47 publications
12
97
1
Order By: Relevance
“…In line with previous studies that documented the discrepancy between subjective insomnia and objective sleep state assessments 28,29 , our results similarly revealed that objective sleep states including total sleep time, day-to-day variation in sleep time, episodes of nocturnal awakening, and sleep latency were not associated with subjective insomnia in middle-aged women. However, in the present study, we found that low sleep efficiency was one of the two factors that independently affect subjective insomnia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous studies that documented the discrepancy between subjective insomnia and objective sleep state assessments 28,29 , our results similarly revealed that objective sleep states including total sleep time, day-to-day variation in sleep time, episodes of nocturnal awakening, and sleep latency were not associated with subjective insomnia in middle-aged women. However, in the present study, we found that low sleep efficiency was one of the two factors that independently affect subjective insomnia.…”
Section: Discussionsupporting
confidence: 93%
“…Polysomnography provides information on body and brain functions during sleep based on electroencephalography, electromyography, and electrocardiography. Due to the documented discrepancy between subjective and objective sleep parameters 28,29 , it is preferable to assess both subjective and objective sleep measures to study sleep disturbances in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Because both approaches result in decreased total sleep time, they appear to primarily promote sleep drive in these patients. In terms of conscious awareness, there is evidence that CBTI reduces subjective-objective sleep discrepancy following treatment [109]. It is possible that CBTI works to suppress conscious awareness during sleep by enhancing sleep drive, thereby reducing sleep discrepancy.…”
Section: Treatmentmentioning
confidence: 99%
“…The discrepancy between subjective reports and objective estimates has been demonstrated in a variety of indices of sleep, including total sleep time (TST) [12,13,14,26], sleep onset latency (SOL) [13,24,27,28,29], wake-time after sleep onset (WASO) [24,28,29], and sleep efficiency (SE) [26,30]. Discrepancy occurs in primary insomnia and also in patient groups where insomnia is comorbid with other health or psychiatric conditions [31,32,33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The tendency for people with insomnia to underestimate objective sleep has been conceptualised in several ways; (i) as an exaggeration of sleep difficulties, perhaps due to more general psychological characteristics and personality traits [19,27]; (ii) as a meaningful phenomenon which reflects a localised sleep disturbance with candidate physiological markers [20,28]; and (iii) as a cognitive distortion which contributes to the maintenance and escalation of insomnia [37]. According to Harvey’s Cognitive Model (2002), those who underestimate their sleep may be more at risk of developing objective sleep deficits due to increased preoccupation with sleep and increased sleep related anxiety and arousal, which is antithetical to optimal sleep onset and maintenance [37].…”
Section: Introductionmentioning
confidence: 99%